2012
DOI: 10.1016/j.bmc.2012.03.043
|View full text |Cite
|
Sign up to set email alerts
|

A highly selective Hsp90 affinity chromatography resin with a cleavable linker

Abstract: Over 200 proteins have been identified that interact with the protein chaperone Hsp90, a recognized therapeutic target thought to participate in non-oncogene addiction in a variety of human cancers. However, defining Hsp90 clients is challenging because interactions between Hsp90 and its physiologically relevant targets involve low affinity binding and are thought to be transient. Using a chemo-proteomic strategy, we have developed a novel orthogonally cleavable Hsp90 affinity resin that allows purification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 47 publications
1
50
0
Order By: Relevance
“…Despite some reduction in affinity, the addition of the tethered components was found to increase specificity by eliminating binding to Grp94 (Figure S2B). Previous work had also shown that the addition of the tether at the ortho -position of the parent ligand reduced the specificity towards recombinant and native Trap-1 (Hughes et al, 2012). These findings suggest that the added steric bulk due to the presence of the tether and added fluor, for example, interferes with the ATP-binding site of Grp94 and Trap-1, but not Hsp90.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite some reduction in affinity, the addition of the tethered components was found to increase specificity by eliminating binding to Grp94 (Figure S2B). Previous work had also shown that the addition of the tether at the ortho -position of the parent ligand reduced the specificity towards recombinant and native Trap-1 (Hughes et al, 2012). These findings suggest that the added steric bulk due to the presence of the tether and added fluor, for example, interferes with the ATP-binding site of Grp94 and Trap-1, but not Hsp90.…”
Section: Resultsmentioning
confidence: 98%
“…We recently reported the development of a cleavable tethered Hsp90 inhibitor and demonstrated its use as an affinity resin(Hughes et al, 2012). When bound to the tethered ligand, Hsp90 could be recovered along with one of its established oncogenic clients, Her2, in a competitive manner.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the histidine-tagged yeast Hsp90 was loaded onto an affinity column [12] and was subsequently tested with these natural product. Mass spectrum analysis of the eluted solutions of proteins resulted in the identification of the compounds bound to Hsp90.…”
Section: Introductionmentioning
confidence: 99%
“…1B and S1A). To determine if the induction of Hsp70i was the result of a general cellular stress in response to DENV infection or likely to be facilitated by the virus itself, we induced expression of the protein in uninfected cells using the Hsp90 inhibitor, HS10 (30). Induction of Hsp70i expression is a signature response to all Hsp90 inhibitors targeting the ATP binding domain of the protein (3436).…”
Section: Resultsmentioning
confidence: 99%
“…HS-72 (27) and HS-10 (30) were synthesized as previously described and Ribavirin was purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%